2015
DOI: 10.1589/jpts.27.2183
|View full text |Cite
|
Sign up to set email alerts
|

Perceived body discomfort and trunk muscle activity in three prolonged sitting postures

Abstract: [Purpose] This study aimed to investigate the perceived discomfort and trunk muscle activity in three different 1-hour sitting postures. [Subjects] A repeated-measures design study was conducted on 10 healthy subjects. [Methods] Each subject sat for an hour in three sitting postures (i.e., upright, slumped, and forward leaning sitting postures). Subjects rated perceived body discomfort using Borg’s CR-10 scale at the beginning and after 1 hour sitting. The electromyographic activity of the trunk muscle activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 35 publications
2
48
0
6
Order By: Relevance
“…In particular, students sitting with an upright pose for more than an hour appear to be users that most likely suffer from Lower Back Pain (LBP) due to compression of the tissue in the lumbar spine (Rajaratnam and Janwantanakul, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, students sitting with an upright pose for more than an hour appear to be users that most likely suffer from Lower Back Pain (LBP) due to compression of the tissue in the lumbar spine (Rajaratnam and Janwantanakul, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A chair with an armrest would provide a higher comfort level in such a way where one can sit with an upright shoulder-relaxed posture and place the arms on the armrest (Rajaratnam and Janwantanakul, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] In addition, prolonged sitting changes body posture, and these in turn affect trunk muscle activity, such as, of the iliocostalis lumborum, multifidus, internal oblique, transverse abdominis muscles. 5 Abdominal muscles play roles in respiration, 6,7 and their activities affect posture, which suggests respiratory function is probably associated with posture. 8 In a previous study, it was suggested that an upright sitting posture is associated with higher internal oblique, transverse abdominis and iliocostalis lumborum muscle activities as compared with a slumped sitting posture.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies reported that prolonged sitting has an adverse influence on musculoskeletal functions. For example, it brings about decreases in intervertebral disk health, active lumbar range of motion, and spinal musculature activity, and an increase in passive stiffness 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%